ALCOHOL INFLUENCES AGGRESSIVE BEHAVIOUR THAT INCREASES LIKELIHOOD OF INITIATING DATING VIOLENCE AMONG MALE YOUTH IN COLLEGES WITHIN WESTERN COUNTRIES: A SCOPING REVIEW - Anis, Muhammad Ariff Aidil Bin Mohd; Pius, Prince Cyrill Sim; Aslam, Muhammad Shahzad (Universal Journal of Pharmaceutical Research, 2019)
The youth demographic are often linked to alcohol consumption, and it is a widespread assumption that consuming alcohol will increase the likelihood of initiating violence. In the United States, alcohol is the most popular psychoactive drug used and contributes to 40% of violent crimes happening in the country. Among the many forms of violence, dating violence or interpersonal violence are often related to alcohol. Dating violence is often caused by male partners. 20% to 30% of male college students physically abuse their dating partners. Thus, this review study proposes the influence of alcohol on behaviour on male youth in Western colleges and the likelihood of dating violence to emerge. Online journals involving alcohol and violence among male college students in Western countries are searched on PubMed. The Western country selected in the studies found is the United States. The studies chosen were randomised and quantitative studies. Hence, the review hopefully serves as a trigger for future policies to consider the dangers of intoxication more seriously and more research should be done regarding the relationship between alcohol and violent behaviour so that interpersonal violence among adolescents can be reduced. Peer Review History: Received 4 August 2019; Revised 9 September; Accepted 30 October, Available online 15 November 2019 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Noha El Baghdady , MTI University, Cairo, Egypt, nohasalah21@yahoo.com